Optimization of phenolic compounds extraction with antioxidant activity from açaí, blueberry and goji berry using response surface methodology - Soares dos Reis, Cristiane de Moura, Amália; Vanderlei Aparecido de Lima, Letícia Dangui da Silva; Cadorin Oldoni, Tatiane Luiza; Pereira, Celeide; Carpes, Solange Teresinha (Emirates Journal of Food and Agriculture, 2018)
The aim of this study was to determine the best extraction conditions of phenolic compounds present in açaí, blueberry and goji berry fruits using the response surface methodology (RSM). The phenolic compounds profile by high-performance liquid chromatography, antioxidant activity was also determined. A factorial 23 design was used to analyze the effect of the solvent (ethanol and water), time (30 and 60 min) and temperature (30 °C and 60 °C) on the extraction of total phenolic compounds (TPC) and activity antioxidant (AA). The variables time and temperature had a positive effect on antioxidant activity (AA) in their highest levels, 60 min and 60 °C, respectively. The solvent ethanol 800 g/mL was more efficient in TPC extracting with AA in all matrices. Rutin was present in high amounts in blueberry and goji berry, and the myricetin in açaí. The açaí showed higher in vitro antioxidant activity when extracted at 60 °C for 60 min. The high correlation coefficient (0.98) of global response (GR) showed that we can find out single and global response in research with multiple dependent variables. The GR analysis indicated the highest values of the TPC and AA when the fruits were extracted at 60°C for 60 min using ethanol as solvent and it was very useful for simplifying and improving the phenolic compounds extraction performance.